Spectrophotometric Assay of Noradrenaline in Pharmaceutical Formulation with Quinalizarin in Aqueous Solution - Thabit S. Al-Ghabsha; Amal M. Saeed (مجلة جامعة الانبار للعلوم الصرفة, 2012)
A simple, rapid and sensitive spectrophotometric method for the determination of noradrenaline was developed. The method is based on the proton transfer reaction with quinalizarin in aqueous neutral solution to form a violet product showing maximum absorbance at 560 nm with molar absorptivity of 6680 l.mol-1.cm-1. The method follows Beer’s law over the concentration range (5.91×10-6 -5.91×10-5) mol.L-1 The accuracy (average recovery) of the method is 99.72% and the precision (RSD) of the method is less than 1.5%.The method was successfully applied for the determination of noradrenaline in pharmaceutical formulation as injection and the results were in a good agreement with the standard addition procedure.